Influenza A/H1N1 Severe Pneumonia: Novel Morphocytological Findings in Bronchoalveolar Lavage - Faverio, Paola; Aliberti, Stefano; Ezekiel, Clinton; Messinesi, Grazia; Brenna, Ambrogio; Pesci, Alberto (Interdisciplinary Perspectives on Infectious Diseases, 2014)
We present the results of bronchoalveolar lavage (BAL) performed in three patients with severe influenza A/H1N1 pneumonia complicated by acute respiratory distress syndrome (ARDS). Light microscopy analysis of BAL cytocentrifugates showed the presence of characteristic large, mononuclear, plasmoblastic/plasmocytoid-like cells never described before. Via transmission electron microscopy, these cells were classified as atypical type II pneumocytes and some of them showed cytoplasmic vesicles and inclusions. We concluded that plasmoblastic/plasmocytoid-like type II pneumocytes might represent a morphologic marker of A/H1N1 influenza virus infection as well as reparative cellular activation after diffuse alveolar damage.